Declining Search Frictions, Unemployment, and Growth - Martellini, Paolo; Menzio, Guido (Journal of Political Economy, 2020)
For a search-theoretic model of the labor market, we seek conditions for the existence of a balanced growth path (BGP), where unemployment, vacancy, and worker’s transitions rates remain constant in the face of improvements in the production and search technologies. A BGP exists iff firm-worker matches are inspection goods and the quality of a match is drawn from a Pareto distribution. Declining search frictions contribute to growth with an intensity determined by the tail coefficient of the Pareto distribution. We develop a strategy to measure the rate of decline of search frictions and their contribution to growth.